Hospital Services And Their Influence On Patient Satisfaction With Emotional Moderation - Dhita Dhora Damayanti; Evi Fitrotun Najiah; Levia Inggrit Sayekti (Sean Institute, 2025)
The topic related to satisfaction with a service is an issue that is still interesting to study. Service quality in the service industry is closely related to the process of forming individual satisfaction. Many phenomena occur, especially in health services in hospitals. Apart from the existing phenomena, it turns out that several studies related to the quality of hospital services that have been conducted previously still found inconsistent results (Kim, 2011; Chandra et al., 2018; Ratnawati, 2020). The inconsistent relationship that has occurred so far requires further explanation related to the causal factors. This inconsistent phenomenon and relationship certainly requires further explanation related to the causal factors. Therefore, the current study was conducted to explain this by conceptualizing emotions as a moderating variable. The research method used was a survey conducted on patients at several private hospitals in Lamongan. Data collection was carried out through a questionnaire on 300 respondents. Furthermore, the data will be analyzed with Partial least Square (PLS). Research results explain that quality measured service with HCSQ Model has significant influence to satisfaction patient. On the side other, variable emo moderator said weaken interaction connection between quality service with satisfaction However No significant.